The impact of specific reverse charge on waste and scrap on tax revenues in the Czech Republic - Eliška Čejková; Hana Zídková (European Financial and Accounting Journal, 2019)
The paper is focused on VAT evasion and especially carousel frauds. It describes the types of VAT evasion, methods of its estimation and measures taken by the European member state to fight it. The aim of the article is to develop a reasonable method for assessing the volume of carousel fraud in the Czech Republic. It uses ex-post calculation of the impact of a specific reverse-charge implemented in the Czech Republic on waste and scrap in 2011. The analysis employs trade balance data of the Czech Republic published by the Czech Statistical Office and a model of the carousel fraud to estimate the size of the carousel fraud existing prior to the implementation of the specific reverse charge in the CR. The volume of the supposed carousels in waste and scrap present in the period from 1 April 2010 to 31 March 2011 in the CR is according to the authors EUR 56 mil. (approx. CZK 1.4 bn.).
Keywords: H26; 650; Carousel fraud; Specific reverse charge; VAT evasion